Qualitative Analysis of a Three-Species Reaction-Diffusion Model with Modified Leslie-Gower Scheme. (4th May 2021) - Wang, Xiaoni; Guo, Gaihui; Li, Jian; Du, Mengmeng
Abstract : The qualitative analysis of a three-species reaction-diffusion model with a modified Leslie-Gower scheme under the Neumann boundary condition is obtained. The existence and the stability of the constant solutions for the ODE system and PDE system are discussed, respectively. And then, the priori estimates of positive steady states are given by the maximum principle and Harnack inequality. Moreover, the nonexistence of nonconstant positive steady states is derived by using Poincaré inequality. Finally, the existence of nonconstant positive steady states is established based on the Leray-Schauder degree theory.